Applied anthropometric for wheelchair user in Malaysia - Adnan, Nursyahirah; Md Dawal, Siti Zawiah (Elsevier, 2019)
Universal design refers to wide range of ideas intended to establish facilities that are naturally applicable to small population like people with disabilities (PWDs), and subsequently, for older people, adults, and children. In that case, an anthropometric database for the Malaysian wheelchair users population should be initiated. A total of 52 participants took part in this study, which involved 41 males and 11 females from Malaysian wheelchair users with their ages ranging from 20 to 50 years old. 15 anthropometric dimensions were defined in designing workstations for wheelchair users. Interviews and surveys were conducted to investigate the problems faced by wheelchair users when using existing workstations in Malaysia. The result from t-test of SPSS software indicated that there are significant differences in the anthropometric dimensions between Malaysian wheelchair users population and Malaysian able-bodied population. The examples of sitting workstations designed based on wheelchair user preferences were also presented in this study. © 2018 Elsevier Ltd